Influência do modo de irrigação na tolerância de plantas ornamentais à salinidade da água - Oliveira, Francisco Ítalo Fernandes de (2016)
World trade of flowers and ornamental plants, of which the most significant branch is cut flowers, followed by the live plants, is an important segment economically to Brazil especially for the Northeast. Although the Northeast region has favorable climatic conditions for the cultivation of flowers and ornamental plants, low quality irrigation water, it is revealed as a problem. The plant species exhibit different mechanisms of tolerance to salt, in some cases, allowing their survival and production. Thus, the research aimed to evaluate the tolerance of four ornamental species to increasing levels of salinity of irrigation water and different modes of supply of water. The research was conducted in a protected environment, in the period from September to November 2015, in the experimental area of the weather station at the University Campus of Pici, the Federal University of Ceará, Fortaleza - Ceará. The treatments were distributed in randomized blocks, arranged in a split plot design with four replications with six levels of salinity of irrigation water to the plots (A1 - 0.6; A2 - 1.2; A3 - 1.8; A4 - 2 4; A5 - 3.0 and A6 - 3.6 dS/m), two modes of irrigation in the subplots (M1 - localized irrigation and M2 - not localized irrigation) and four ornamental species in subsubplots (E1 - Catharanthus roseus; E2 - Allamanda cathartica; E3 - Ixora coccinea and E4 - Duranta erecta), with 48 plants in each block, totaling one hundred ninety-two experimental units. The seedlings of ornamentals were transferred to plastic pots with a volume of 7 liters filled with a gravel layer and substrate, comprising a mixture of sand and earthworm humus, in the ratio 2:1 respectively. They were evaluated biometric, physiological, nutritional and sensorial parameters in plants. The most appropriate variables to classify the species as tolerance to salinity, are related to biomass production. The species are more sensitive to the irrigation method not located than the localized mode. The species that are more tolerant to salinity of irrigation water were Catharanthus roseus and Ixora coccinea.